Critical Care Nurses’ Experiences of End-of-Life Care: A Qualitative Study - Utami, Reni Sulung; Pujianto, Ahmat; Setyawan, Dody; Naviati, Elsa; Rochana, Nana (Nurse Media Journal of Nursing, 2020)
Background: Patients admitted to the intensive care unit (ICU) may face terminal illness situations, which may lead to death. In this case, the role of critical care nurses shifts from life-sustaining to end-of-life care (EOLC). Nurses’ involvement in EOLC varies between countries, even in one country due to differences in religion, culture, organization, laws, cases and patient quality. In Indonesia, research on EOLC in ICU has not been carried out.Purpose: This study aimed to explore the experiences of critical care nurses in providing EOLC.Methods: A qualitative study with a phenomenological approach was conducted. Ten critical care nurses having the experiences of caring for dying patients were recruited through a purposive sampling technique for in-depth interviews. Manual content analysis was used to identify themes.Results: The results of the study found five themes, including the challenge of communication with the family, support for the family, support for the patient, discussion and decision making, and nurses’ emotions. Conclusion: Most of EOLC provided by critical care nurses was focused on the family. They had some challenges in communication and decision making. Nurses need to get training and education about how to care for patients towards the end of life.